2018
DOI: 10.1155/2018/8346319
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Rice Husk Ash as Cementitious Material in High‐Strength Cement‐Admixed Clay

Abstract: e potential and efficiency of using rice husk ash (RHA) to add up or partially replace Portland cement in deep cement mixing technique are examined. A series of unconfined compression tests on cement-RHA-stabilized clay are conducted to investigate the influence of RHA on the mixture properties. Special attention is paid to its efficiency for increasing the strength by partial cement replacement to obtain high-strength soil cement, and it is compared with fly ash. Test results indicate that up to 35% of RHA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 34 publications
3
45
0
1
Order By: Relevance
“…The study founds interesting results after mixing RHA in clay with cement. The results suggest that favourable results could be obtained by adding 35% RHA and 10% cement in clay [26]. The partial replacement of cement by Rice Husk was also studied by other authors such as Bhusan R. et.al (2017).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The study founds interesting results after mixing RHA in clay with cement. The results suggest that favourable results could be obtained by adding 35% RHA and 10% cement in clay [26]. The partial replacement of cement by Rice Husk was also studied by other authors such as Bhusan R. et.al (2017).…”
Section: Introductionmentioning
confidence: 63%
“…Many researches are carried out on utilizing of industrial waste/agricultural waste such as fly ash, corn cob ash, metakaolin, bagasse ash and RHA during past two decades such as [23][24][25][26]. Rice Husk is also utilised in clay to increase the unconfined compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…Another examination demonstrated that the strength of cement blended with clay was increased by over 100% at 28 days and this phenomenon was mainly ascribed due to presence of the RHA particles. At curing times of 14 and 28 days, RHA displays greater proficiency on Portland concrete substitution when the cementitious substance is at the very least 20% and 35% [99]. The impact of ligno-sulfonate (LS) and CaCl 2 has been examined on the setting times, with the accumulation of 2% of CaC1 2 , 1% ligno-sulfonate (LS) and 1% ligno-sulfonate (LS) + 2% CaCl 2 .…”
Section: Setting Timementioning
confidence: 99%
“…Sandhu and Siddique173 concluded that RHA acts as a concrete filler with reduced land‐filling costs and also provides a cleaner sustainable environmental solution, saving energy and reducing carbon dioxide generation by cement consumption. The ground ash of RH is partially filled in cement concrete, which improves the properties of the concrete 174. The addition of the 10 wt% RHA in composite can improve the compressive strength, fire, and acid resistance of the as‐prepared composite, which is suitable for making load‐bearing bricks for buildings 175.…”
Section: Second Generation Agricultural Wastes and Their Usesmentioning
confidence: 99%